2021
DOI: 10.26434/chemrxiv-2021-jvbfl
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen properties in an organic molecule revealed by XFEL and electron crystallography

Abstract: Structure analysis of small crystals is important in synthetic organic chemistry, pharmaceutical and material sciences, and related areas, as the conformation of these molecules may differ in large and small crystals, thus affecting the interpretation of their functional properties and drug efficacy. From small crystals, X-ray and electron beams could furnish electron densities and Coulomb potentials of target molecules, respectively. The two beams provide distinctly different information, and this potential h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The electron beam makes the hydrogen densities appear even slightly further from the bonded atom than the nucleus of hydrogen (3,27). We have shown that in the Coulomb potential map of an organic molecule the hydrogen density peak position depends on the type of covalent bond (27). There is a larger change in the position of the hydrogen peaks in electron density maps depending on the polarity of bonding due to the mobility of electrons (29,30,31).…”
Section: Hydrogen Propertiesmentioning
confidence: 92%
See 4 more Smart Citations
“…The electron beam makes the hydrogen densities appear even slightly further from the bonded atom than the nucleus of hydrogen (3,27). We have shown that in the Coulomb potential map of an organic molecule the hydrogen density peak position depends on the type of covalent bond (27). There is a larger change in the position of the hydrogen peaks in electron density maps depending on the polarity of bonding due to the mobility of electrons (29,30,31).…”
Section: Hydrogen Propertiesmentioning
confidence: 92%
“…In single particle reconstructions and Coulomb potential maps by 3D ED, hydrogen densities appear further away from their parent atoms than those in X-ray crystal structures (28,3,27). This reflects the fact that incident electrons are affected by both electrons and nuclear charges and the latter is dominant, while X-rays are scattered by electrons around atoms and the electron in a hydrogen atom is attracted towards its parent bonded atom (29,30).…”
Section: Hydrogen Propertiesmentioning
confidence: 96%
See 3 more Smart Citations